Individual acceleration-speed profile in-situ: A proof of concept in professional football players - Morin, J.-B.; Le Mat, Y.; Osgnach, C.; Barnabò, A.; Pilati, A.; Samozino, P.; Di Prampero, P. E. (Journal of Biomechanics, 2021)
Assessing football players` sprint mechanical outputs is key to the performance management process (e.g. talent identification, training, monitoring, return-to-sport). This is possible using linear sprint testing to derive force-velocity-power outputs (in laboratory or field settings), but testing requires specific efforts and the movement assessed is not specific to the football playing tasks. This proof-of-concept short communication presents a method to derive the players` individual acceleration-speed (AS) profile in-situ, i.e. from global positioning system data collected over several football sessions (without running specific tests). Briefly, raw speed data collected in 16 professional male football players over several training sessions were plotted, and for each 0.2 m/s increment in speed from 3 m/s up to the individual top-speed reached, maximal acceleration output was retained to generate a linear AS profile. Results showed highly linear AS profiles for all players (all R2 > 0.984) which allowed to extrapolate the theoretical maximal speed and accelerations as the individual`s sprint maximal capacities. Good reliability was observed between AS profiles determined 2 weeks apart for the players tested, and further research should focus on deepening our understanding of these methodological features. Despite the need for further explorations (e.g. comparison with conceptually close force-velocity assessments that require, isolated and not football-specific linear sprint tests), this in-situ approach is promising and allows direct assessment of football players within their specific acceleration-speed tasks. This opens several perspectives in the performance and injury prevention fields, in football and likely other sprint-based team sports, and the possibility to "test players without testing them".